(untitled) (Albayan Scientific Journal, 2023)
The Search aims to test and analyze the causal relationship between money supply and inflation in the Libyan economy during the period 1990-2020 using the VAR methodology. A number of external variables have been included real GDP growth rate (RGDP), economic blockade (BLO), security situation (REV), ratio of monetary wealth to total wealth (k) which are expected to affect the nature of the relationship between the variables of money supply and inflation in the Libyan economy Johansson’s cointegration test results indicated that there is no causal relationship between the money supply and the long-run inflation rate. Whereas, the Wald Test indicated that there is a two-way causality in the short term between the decelerated values ​​of each variable and the current values ​​of the other variable. The study recommends that the Central Bank of Libya should adopt a flexible monetary policy towards the money supply, and strip commercial banks of their ability to influence that supply by enacting legislation that limits their ability to grant credit except through depositors’ savings, in order to achieve economic stability.